Adsorptive Removal of Mercury by Zeolites and Montmorillonite - Abdillah, Andi Massoeang; Abidin, Zaenal; Widiatmaka, Widiatmaka; Johan, Erni; Matsue, Naoto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
The environmental pollution by the drainage containing heavy metals such as Hg is a serious problem in mining activities in Indonesia. We examined the effect of coexisting thiourea on the adsorptive removal of Hg by zeolites and montmorillonite. To a 100 mL of 10 mg/L (0.05 mM) HgCl2 solution in the absence and presence of 0.5 mM thiourea, different amounts of zeolite (A4, P or mordenite) or montmorillonite was added, shaken for 24 h, centrifuged, and supernatant Hg2+ concentration was measured. In the absence of thiourea, the ratio of the negative charges in the adsorbents to the positive charges in Hg2+, Ads/Hg ratio, needed to attain >80% Hg2+ removal were >70 for mordenite, >1625 for P, >600 for A4, and montmorillonite showed no Hg2+ adsorption. In contrast, in the presence of thiourea, nearly 100% removal was attained at lower Ads/Hg ratios: the ratios were 1 for montmorillonite,